PERAN BANK PEMBIAYAAN RAKYAT SYARIAH DALAM MENGEMBANGKAN USAHA MIKRO KECIL MENENGAH DI KECAMATAN MANGGAR (STUDI PADA BPRS CABANG MANGGAR) - Miftah - Farizqi (UIN Mataram, 2021)
The presence of the Sharia People's Financing Bank (BPRS) Manggar Branch as an identical bank prioritizes financing productsi withi thei aimi ofi improvingi thei economici welfare of the people, especially the weak economic community, (UMKM financing). The development of UMKM is very influential on the economy, especially in Manggar District, so UMKMs are supposed to be empowered by providing financial assistance, one of which is through Islamic banking. The typei ofi thisi researchi isi descriptivei qualitative. i Datai collectioni techniques consisti ofi observation, documentation, and interviews. While thei datai analysisi techniqueiused is interactive model analysis, which consists of data collection, datai reduction, datai presentation, iandi drawing conclusions.The results of this study indicate that the growth of UMKM customers has decreased with an indicator of the number of customers from 2016-2018 as many as 725 people. The development system used is: First, sustaining the economic sector of the Manggar community. Second, increase the allocation of UMKM financing. Third, carry out monitoring of the customer. Fourth, as a consultant in developing customer businesses.